The Negative Existential Cycle In Ancient Egyptian - Oréal, Elsa (My University, 2022)
Ancient Egyptian has a very long attested history, which allows us to follow the emergence and evolution of several negative patterns. In spite of the inherent obstacles in a dead language's documentation, my research – focusing on negation in Earlier Egyptian (roughly defined as the language of texts written from 3000 to 1300 BCE) but tracing the relevant forms until Coptic (the last phase of the language, written in the Greek alphabet from the 4th to 14th century CE) – sheds light on a renewal process that appears to belong to the category of the negative existential cycle. This process has long remained misunderstood, but recent progress in the field of linguistic typology regarding linguistic change in the negative domain makes it possible to propose a coherent historical analysis of the data. Starting with a transitional phase (C--A) documented in Old Egyptian, the Egyptian negative existential cycle does not illustrate Croft's model in an ideal way. However, it offers a concrete case for a better understanding of how structural and functional parameters are intertwined in explaining this type of evolution.
Keywords: Ancient Egyptian; Negative existential Cycle; Nominalization